Implementasi Pengggunaan Media Film Untuk Meningkatkan Keaktifan Belajar Peserta Didik Sekolah Dasar - Salsabila, Annisa; Triawan, Hafid; Yessi Desmatala Sari, Yessi; Supriyadi, Supriyadi; Hermawan, Jody Setya (Universitas Hamzanwadi, 2024)
Learning media is an important requirement in the learning process to achieve the desired learning objectives. One of the learning media used in elementary school is animated movie media animation The purpose is to make it easier for educators to carry out learning and increase the activeness of students. In the research conducted using qualitative methods conducted by interviews to obtain maximum information. The results of the interviews conducted stated that learning using movie media can also encourage students to be more active and increase their response in the learning process. The activeness of learners can affect the conditions of the learning environment, so that the activeness of learning that arises in students will encourage an effective and interesting learning process. Some constraints will certainly arise, as well as the need for other supporting tools, sufficient knowledge in the use of these media and the need for adjustments to the character of the learners. Therefore, it can be justified that the use of appropriate learning media will help achieve maximum learning objectives